Distributed access control on IoT ledger-based architecture - Lunardi, Roben Castagna; Michelin, Regio Antonio; Neu, Charles Varlei; Zorzo, Avelino Francisco (NOMS 2018 - 2018 IEEE/IFIP Network Operations and Management Symposium, 2018)
Due to increased number of attacks on the Internet of Things (IoT) devices, the security of IoT networks became critical. Some recent researches proposed the adoption of blockchain in IoT networks without a thorough discussion on the impact of the solution on the devices performance. Furthermore, blockchain employment in the context of IoT can be challenging due to the devices hardware limitations. To fill this gap, this paper proposes an IoT ledger-based architecture to ensure access control on heterogeneous scenarios. This research applies conventional devices used on IoT networks, such as Arduino, Raspberry and Orange Pi boards. Finally, we perform performance evaluation focused on access control of IoT devices and on information propagation through peers on a private IoT network scenario.